Toward a more sustainable coffee production - Muhammad Ibnu; Astrid Offermans; Pieter Glasbergen (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2019)
This paper contributes to the literature on the emerging trend of Southern sustainability standards and certifications as a reaction to the Northern-based private standards by businesses and NGOs. It particularly analyzes the implementation capacity of ISCoffee as a public standard and certification initiated by the Indonesian government. We analyze the opportunities and barriers in the process of implementing ISCoffee and examine whether ISCoffee can become a viable alternative to Northern-based private standards and certification. We first conclude that the implementation capacity of ISCoffee is low, because of weak administrative structures, and communication and coordination deficiencies. Second, we conclude that ISCoffee will unlikely being able to solve smallholder-related problems in the coffee sector such as limited access to market, insufficient capital, and underdeveloped farmer organizations. Finally, we conclude that ISCoffee - on the short term - will not manage to become a viable alternative to Northern-based private standards and certifications.